Risk Stratification to Define the Role of Radiotherapy for Benign and Atypical Meningioma: A Recursive Partitioning Analysis. Issue 5 (11th May 2022) - Chang, Won Ick; Kim, Il-Han; Choi, Seung Hong; Kim, Tae Min; Lee, Soon-Tae; Won, Jae Kyung; Park, Sung-Hye; Kim, Min-Sung; Kim, Jin Wook; Kim, Yong Hwy; Park, Chul-Kee; Lee, Joo Ho
Abstract : BACKGROUND: The role of adjuvant radiotherapy (RT) for benign or atypical meningioma is controversial. OBJECTIVE: To identify prognostic factors and a subgroup that could be potentially indicated for adjuvant RT. METHODS: A total of 336 patients with benign and 157 patients with atypical meningioma underwent surgical resection between January 2015 and December 2019. We retrospectively analyzed 407 patients who did not receive adjuvant RT to stratify risk groups for recurrence. A recursive partitioning analysis (RPA) with the prognostic factors for their failure-free survival (FFS) divided the patients into risk groups. RESULTS: The 3-year FFS with surgical resection only was 76.5%. Identified prognostic factors for FFS were skull base location, tumor size, brain invasion, a Ki-67 proliferation index of ≥5%, and subtotal resection. The RPA-classified patients were divided into 4 risk groups: very low, low, intermediate, and high, and their 3-year FFS were 98.9%, 78.5%, 59.8%, and 34.2%, respectively. Intermediate-risk and high-risk groups comprise the patients with meningioma of sizes ≥2 cm after subtotal resection or meningioma of sizes >3 cm, located in the skull base or with brain invasion, respectively. After combining with patients treated with adjuvant RT, no FFS benefit was found in the very low-risk and low-risk groups after adjuvant RT, whereas significantly improved FFS was found in the intermediate-risk and high-risk groups ( P < .05). CONCLUSION: The RPA classification revealed a subgroup of patients who could be potentially indicated for adjuvant RT even after gross total resection or for whom adjuvant RT could be deferred.